ASSESSMENT OF IMMUNOMODULATORY POTENTIAL OF AN AYURVEDIC FORMULATION, NIROCIL SYRUP IN WISTAR RATS - GHADIGAONKAR, DINESH DILIP; CHAWDA, MUKESH B; THAKUR, KAPIL S (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aims to assess the immunomodulatory potential of an Ayurvedic formulation, Nirocil syrup, in Wistar rats. Methods: The experiments were conducted on Wistar rats with prior approval from the Institutional Animal Ethics Committee. Nirocil syrup was administered for 6 weeks to experimental animals. Parameters such as hemagglutination titer, histopathology of immunological organs, complete blood count, differential leukocyte count, and immunological paw edema were recorded and compared with controlled (untreated) and becozinc treated groups. Results: Nirocil treated group significantly enhanced the antibody titer in comparison to the control group. The results are supported by the increase in blood lymphocyte count and antigenic stimulation in immunological organs (spleen). Nirocil syrup enhanced antibody formation and suppressed the immunological edema in experimental animals. Conclusions: The study concludes that the Ayurvedic formulation Nirocil syrup has immunopotentiating activity.